ENERGY SAVING BEHAVIOR IN DRIVING AND MARKRTING MIX IN THE CONSUMER’S PERSPECTIVE ON ELECTRIC VEHICLE OF PASSENGER CARS IN CENTRAL REGION - โนนทิง, เมธา; หิรัญญสมบูรณ์, กตัญญู (Journal of KMITL Business school, 2019)
The objectives of studying about passenger car drivers’ energy conservation behavior and perspectives of passenger car drivers by using questionnaires to collect data. Statistical analysis is Average frequency, standard deviation And using the hypothesis testing by Chi-square test. Paired by Fisher’s Least Significant Difference (LSD) method. The result found that the majority of the participants are married men between the ages of 31 and 40, with child or children, with 3 to 5 family members, graduated with bachelor’s degree, work as a company employee and have monthly car fuel expense from 1,501 baht to 5,200 baht. The participants have daily driving energy conservation behavior with a purpose of reducing car fuel expense approximately 1,000 baht per month by switching to consume fuel with cheaper prices. The participants’ perspectives on electric vehicles when considering 4C’s Marketing Mix reveal that the participants demand public relations communication, government support and the number of vehicle electric charging stations to create their confidence to use electric vehicles. The study results about the relationship between the respondents’ personal factors and personal car drivers’ perspectives on electric vehicles show that the differences of gender, age, occupation, income and marital status lead to the different perspectives on electric vehicles. On the other hands, education level and number of family members do not have relationship with persona car drivers’ perspectives on electric vehicles. In addition, the findings also expose that passenger car drivers’ energy conservation behavior has relevant relationship with personal car drivers’ perspectives on electric personal vehicles. The minor energy conservation behaviors are fuel filling frequency and fuel expense that can be reduced. The objectives of energy conservation have relationship only with consumers’ demand and cost that can be saved.